THE EFFECTIVENESS OF SPINNING WHEEL GAMES IN INTRODUCING ENGLISH VOCABULARY IN CHILDREN IN KINDERGARTEN - Novela, Difa Jeni; Muryanti, Elise (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2023)
This study aims to determine the effectiveness of the spinning wheel game in introducing English vocabulary to early childhood at Fadhilah Amal 3 Kindergarten, Padang City. In this study, 20 children were taken as research objects, where 10 children came from the control group and 10 children came from the experimental group. This study uses a quasi-experimental research method in which there is a pre-test and post-test control group. Data collection techniques used in this study were tests and observations. The sampling technique in this study is cluster sampling. Testing the research instrument used a validation test with professional judgment to find out the results with the help of SPSS 19.0 using the alpha Cronbach technique. Testing the hypothesis using statistical techniques T-test with the help of SPSS 19.0 for Windows which shows a significance level of 0.002 < 0.05. Obtaining an effect size of 1.77 is concluded to be included in the high category, thus the spinning wheel game in the introduction of English vocabulary is significantly effective.